Focusing on the bottom contact: Carbon quantum dots embedded SnO2 electron transport layer for high-performance and stable perovskite solar cells. (April 2023) - Liu, Jing; Yin, Yanfeng; He, Bingchen; Wang, Pengfei; Wang, Minhuan; Cai, Wanxian; Han, Yaling; Su, Zhenhuang; Guo, Jingya; Cai, Rui; Jin, Shengye; Gao, Xingyu; et al.
Abstract: Rapid progress has been made to achieve high power conversion efficiency (PCE) of metal halide perovskite solar cells in recent years. However, the unsatisfying operational stability still acts as the key factor that obstructs their successful commercialization. Although numerous strategies including grain boundary passivation, surface post-treatment, and processing management have been widely applied to enhance the stability of the perovskite solar cells with n-i-p structure, the significance of the bottom contact between electron transport layer (ETL) and perovskite is usually overlooked. Herein, we report a SnO2 ETL embedded with carbon quantum dots (CQDs) that largely improves the bottom interface between the perovskite layer and ETL. The multiple positive effect of CQDs in interfacial modulation were confirm by a variety of sophisticated characterizations. The PCE increased from 21.62% to 24.05% owing to the facilitated charge extraction. Notably, the perovskite solar cells with the CQD-SnO2 ETL retained over 84% of their initial PCE after 1000-h continuous irradiation under 1-sun illumination by suppressing the perovskite degradation starting from the bottom contact. This work provides a facile and efficient interface modification method for improving the performance and operational stability of FAPbI3 -based PSCs. Graphical abstract: Image 1 Highlights: The CQDs was embedded into the SnO2 ETL for high-performance PSCs. A holistic improvement on ETL and bottom perovskite contact was demonstrated. The positive effect of CQDs in interfacial modulation was confirmed. The PCE increased significantly and the PSCs exhibited impressive operational stability. This work provides a facile and efficient interface modification method for PSCs.